HIV Prevention After Discontinuing Pre-Exposure Prophylaxis: Conclusions From a Case Study - Jonas, Kai J.; Yaemim, Natthakhet (Frontiers in Public Health, 2018)
Pre-exposure prophylaxis (PrEP) with tenofovir disoproxil fumarate in combination with emtricitabine (FTC) is a highly effective form of HIV prevention. Endeavors of health-care providers and activists in many countries over the world are directed at making access to PrEP possible, or increasing PrEP use among men-who-have-sex-with-men (MSM). We argue while this effort is necessary, we also need to consider modes of HIV prevention after a period of PrEP use. PrEP uptake is not a one-way street, meaning that individuals may discontinue PrEP use, either voluntarily and involuntarily. Voluntary discontinued PrEP use in conjunction with decreased or no HIV risk exposure is unproblematic, but involuntary discontinuations with continuous high level of HIV risk exposure calls for tailored post-PrEP use HIV prevention. We present a case study of an MSM individual who discontinued PrEP for medical reasons (renal function) and seroconverted soon afterward, to illustrate the need for tailored HIV prevention post-PrEP. Furthermore, we provide additional contexts of PrEP discontinuation leading to populations that are in need for post-PrEP types of HIV prevention. Subsequently, we present suggestions for modes of post-PrEP HIV prevention based on knowledge–communication–choice model. Community organization and health-care providers should consider and prepare their HIV prevention consulting protocols for such types of clients and add post-PrEP HIV prevention measures to their consulting offer.